Shaping research for people living with co‐existing mental and physical health conditions: A research priority setting initiative from the United Kingdom - Olivia Taylor; Elizabeth Newbronner; Helen Cooke; Lauren Walker; Ruth Wadman (Wiley, 2024)
Abstract Introduction Those with severe and enduring mental ill health are at greater risk of long‐term physical health conditions and have a reduced life expectancy as a result. Multiple factors compound this health inequality, and the need for setting research priorities in this area is highlighted with physical and mental healthcare services being separate, and limited multimorbidity research. Methods The aim of this exercise was to work in partnership with healthcare professionals and carers, family, friends and individuals with lived experience of both mental and physical health conditions, to set research priorities to help people with mental health conditions to look after their physical health. The exercise was guided by the James Lind Alliance approach. For this, a steering group was set up, two surveys were completed and a final priority workshop was conducted. Results This priority setting exercise guided by people's needs and lived experience has produced a set of well‐defined research topics. Initially, 555 research questions were suggested in the first survey, which were refined to 54 questions for the second survey. A priority setting workshop was then conducted to get the final 10 priorities. Conclusions Taking these topics forward to improve services and treatment for both mental and physical ill health may in turn improve physical health and lessen the reduced life expectancy of those living with mental ill health. Patient or Public Contribution This work was completed in collaboration with people who have lived experience of mental ill health and physical health conditions, as well as carers, family and friends. Their contribution has been significant for this work from piloting surveys, amending language used and educating the researchers and contributing to this paper. The initial work was completed with a steering group and continued with surveys and workshops.